Pollination control in relation to seed yield and effect of temperature on pollen viability of maize (Zea mays) - Roy, S K; Rahman, S M L; Salahuddin, A B M (The Indian Journal of Agricultural Sciences, 2012)
A field experiment was conducted during winter season of 1990-91 and 1991-92 to determine the effect of pollination controlon seed yield and yield components, and of temprature on pollen viability of 'Barnali' maize (Zea mays L.). Compared withopen-pollinated ones, the ears covered with perforated polyethylene bags before silking stage (control) produced only 33%seeds/ear and gave 41% less seed yield. The plants with regular removal of silk before pollen shedding (semi- control)produced 73% seeds/ear and gave 80% seed yield compared with open-pollinated ones which produced 8.06 tonnes/ha. The controlgave 8% more 1000-seed weight and the semi-control 3% more compared with open-pollinated plants. Pollen viability decreasedsignificantly with increase in temperature, but the duration or specific temperature regime did not show any significanteffect. Translocation of stem reserves at pre-silking to developing seed and harvest index in the control and semiÂ·controlplants were significantly lower than in the open-pollinated plants.